2012
DOI: 10.1097/brs.0b013e3182326305
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Behavior of a Biomimetic Artificial Intervertebral Disc

Abstract: A strong and durable AID design was introduced. Compared with current clinical articulating AIDs, this biomimetic AID introduces the natural disc annulus-nucleus structure, resulting in axial behavior closer to that of the natural disc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 39 publications
0
29
0
Order By: Relevance
“…Van der Broek et al (2012a) demonstrated that the Biomimetic Artificial Intervertebral Disc axial dynamic stiffness, for 0.01 Hz to 10 Hz range, was between 3.0 kN/mm to 4.7 kN/mm; this range was within the standard deviation range of the natural intervertebral disc tested by Smeathers and Joanes (1988). Alongside the variation in material properties, the differences between the dynamic stiffness of the intervertebral disc replacement studies (Benzel et al, 2011;Dahl et al, 2011;van den Broek et al, 2012a) and the present study are also a result of testing differences.…”
Section: Discussionmentioning
confidence: 93%
“…Van der Broek et al (2012a) demonstrated that the Biomimetic Artificial Intervertebral Disc axial dynamic stiffness, for 0.01 Hz to 10 Hz range, was between 3.0 kN/mm to 4.7 kN/mm; this range was within the standard deviation range of the natural intervertebral disc tested by Smeathers and Joanes (1988). Alongside the variation in material properties, the differences between the dynamic stiffness of the intervertebral disc replacement studies (Benzel et al, 2011;Dahl et al, 2011;van den Broek et al, 2012a) and the present study are also a result of testing differences.…”
Section: Discussionmentioning
confidence: 93%
“…Nucleus replacement technology, available since the 90’ (PDN, Raymedica Inc., Minneapolis, USA), had good clinical results initially, followed by complications related to subsidence and extrusion. As a result, many other implants have been created, ,, only a few reaching the market, ,− and most are no longer in use. The reason is that although they achieve biomechanical restoration close to but not equal to an intact intervertebral disc, ,,, extrusion and subsidence are not fully solved yet. ,,,, …”
Section: Discussionmentioning
confidence: 99%
“…Moving toward a consensus will greatly improve the ability to compare findings across studies and evaluate potential therapeutic strategies. 312,313 5 However, the following list of best practices was developed based on the scientific rationale summarized from the available literature for mechanical testing of motion segments.…”
Section: Conclusion From Literature Reviewmentioning
confidence: 99%